Pronomina Persona Bahasa Aceh dan Persesuainnya - M,Pd, Drs. Jakfar IS (JURNAL VARIASI, 2010)
In this short explanation, writer explain about personal pronoun in Achenese and agreement. The first explanation is a short description about pronoun, kinds of pronoun, and the examples. Explanation continued about personal pronoun in Achenese which consists of first, second, and third personal pronoun. In this paper also explained about agreement of personal pronoun with the result that seem different between personal pronoun in Achenese and in Indonesian. In addition, in this paper also explained about variation in using personal pronoun and the agreement in West Aceh. This explanation have something as a purpose to escalating our knowledge about variation in using personal pronoun in Achenese.Keyword: personal pronoun, Achenese